2020
DOI: 10.1186/s13068-020-01834-5
|View full text |Cite
|
Sign up to set email alerts
|

A thermostable bacterial lytic polysaccharide monooxygenase with high operational stability in a wide temperature range

Abstract: Background Lytic polysaccharide monooxygenases (LPMOs) are oxidative, copper-dependent enzymes that function as powerful tools in the turnover of various biomasses, including lignocellulosic plant biomass. While LPMOs are considered to be of great importance for biorefineries, little is known about industrial relevant properties such as the ability to operate at high temperatures. Here, we describe a thermostable, cellulose-active LPMO from a high-temperature compost metagenome (called mgLPMO10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 63 publications
3
18
0
Order By: Relevance
“…The apparent melting temperatures of the isolated CBMs were 57.2 °C for CjCBM5 and 75.4 °C for CjCBM73, whereas the apparent melting temperature of the CjLPMO10A CD was 70.2 °C. In accordance with previous studies on the effect of copper binding on the stability of AA10 (30,31) and AA9 (32) LPMOs, the apo variant of CjLPMO10A CD showed reduced stability (Tm,app = 56.6 °C).…”
Section: Thermal Stability and Oxidative Performancesupporting
confidence: 92%
“…The apparent melting temperatures of the isolated CBMs were 57.2 °C for CjCBM5 and 75.4 °C for CjCBM73, whereas the apparent melting temperature of the CjLPMO10A CD was 70.2 °C. In accordance with previous studies on the effect of copper binding on the stability of AA10 (30,31) and AA9 (32) LPMOs, the apo variant of CjLPMO10A CD showed reduced stability (Tm,app = 56.6 °C).…”
Section: Thermal Stability and Oxidative Performancesupporting
confidence: 92%
“…Moreover, the thermostability of other LPMOs of the AA9 family, like those from Scytalidium thermophilum, Malbranchea cinnamomea, Myceliophthora thermophila [44,45], or Talaromyces cellulolyticus [46] are similar to that determined for TamAA9A. However, the most thermostable LPMOs are the bacterial LPMOAA10s found in a compost metagenome (mgLPMO10), with a melting temperature of 83 • C [47]. Despite this, due to the combination of thermostability and good pH tolerance of T. amestolkiae LPMO variants, we postulate they may be promising catalysts for lignocellulosic biomass valorization, since they are stable at the operational temperature used in industrial saccharification, where substrates are usually pretreated with alkali or diluted acid [48].…”
Section: Comparative Physicochemical Properties Of Tamaa9a Variants C...mentioning
confidence: 69%
“…Even though Forsberg et al [79] did not measure the DS values for synergism during these studies, our calculations from their glucose/gluconic acid data suggest that a DS value of about 2.3 AU was achieved. In addition, Tuveng et al [26] also demonstrated that LPMO10 synergized with Cel48A and Cel6B, displaying a DS value of about 1.2 AU during Avicel hydrolysis. It is worth noting that, to date, most studies have focused on fungal cellulase-LPMO synergism-but few have focused on bacterial cellulase-LPMO synergism.…”
Section: Cellulase and Lpmo Synergismmentioning
confidence: 99%
“…Both bacterial and fungal LPMOs have similar structures and mechanisms of action [23]. The catalytic domain of LPMOs can also be attached to CBMs by a flexible linker [24,26]. Furthermore, Isaksen et al [27] demonstrated that the fungal LPMO-AA9C, sourced from Neurospora crassa, was capable of cleaving polymeric cellulose and cello-oligosaccharides with a degree of polymerization of about four to six.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation